2012
DOI: 10.1021/jf3007008
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Inflammation with Foods

Abstract: Constant overproduction of pro-inflammatory molecules leads to chronic inflammation. Unlike acute inflammation, which is essential for healing, chronic inflammation can delay healing and, if left unchecked, contribute to a host of diseases. There is growing evidence that some dietary factors can play important roles in maintaining health and even reversing the progression of chronic diseases, with anti-inflammatory effects as important underlying mechanism. Such findings add to the body of evidence that certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 156 publications
0
65
0
1
Order By: Relevance
“…This dietary advice comes from many epidemiological studies and associated meta-analyses that strongly support the concept that long-term consumption of a diet rich in plant-based foods promotes health by attenuating or delaying the onset of various non-commutable diseases, including cardiovascular diseases, T2D, IR, certain cancers, and several other age-related degenerative disorders. This association has been ascribed partly to the presence of polyphenols that are plant secondary metabolites found in various amounts in the so called polyphenols rich-foods (PRF) such as fruit and vegetables, cereals, and plant-derived foodstuffs, including green tea, black tea, red wine, coffee, chocolate, olives, extra virgin olive oil, and others [43,[209][210][211][212][213]. Herbs and spices, nuts and algae are also potentially prominent in supplying certain polyphenols [36,42,43,[214][215][216].…”
Section: Dietary Polyphenolsmentioning
confidence: 99%
“…This dietary advice comes from many epidemiological studies and associated meta-analyses that strongly support the concept that long-term consumption of a diet rich in plant-based foods promotes health by attenuating or delaying the onset of various non-commutable diseases, including cardiovascular diseases, T2D, IR, certain cancers, and several other age-related degenerative disorders. This association has been ascribed partly to the presence of polyphenols that are plant secondary metabolites found in various amounts in the so called polyphenols rich-foods (PRF) such as fruit and vegetables, cereals, and plant-derived foodstuffs, including green tea, black tea, red wine, coffee, chocolate, olives, extra virgin olive oil, and others [43,[209][210][211][212][213]. Herbs and spices, nuts and algae are also potentially prominent in supplying certain polyphenols [36,42,43,[214][215][216].…”
Section: Dietary Polyphenolsmentioning
confidence: 99%
“…The anti-inflammatory diets have been described on the basis of a Mediterranean dietary pattern 7, 8 . Individuals with a high consumption of vegetables, fruits, whole grains, nuts, seeds, healthy oils, and fish may have a low risk of inflammation-related diseases 9 . Adopting healthy dietary pattern may be the first step in reducing inflammation-associated chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that different foodstuffs can mitigate inflammation in human tissues, thus attenuating the risk of chronic diseases (33). It is thus essential before ingesting plant-based food to know the composition, which can only be accessed by a global proteomics analytical approach.…”
Section: Plants As Basis For Foodmentioning
confidence: 99%